Behavior of functionally graded carbon nanotube reinforced composite sandwich beams with pultruded GFRP core under bending effect - Emrah Madenci; Yasin Onuralp Özkılıç; Yasin Onuralp Özkılıç; Yasin Onuralp Özkılıç; Alireza Bahrami; Ibrahim Y. Hakeem; Ceyhun Aksoylu; Muhammad Rizal Muhammad Asyraf; Alexey N. Beskopylny; Sergey A. Stel’makh; Evgenii M. Shcherban’; Sabry Fayed (Frontiers in Materials, 2024)
A novel generation of composite sandwich beams with laminated carbon fiber-reinforced polymer skins and pultruded glass fiber-reinforced polymer core materials was examined for their flexural behavior. The strength and failure mechanisms of the composite sandwich beams in flatwise and edgewise configurations were investigated using three-point static bending tests. These sophisticated composite structures must be designed and used in a variety of sectors, and our research provides vital insights into their performance and failure patterns. In comparison to the reference specimens (FGM-1), the carbon nanotube-reinforced specimens’ bending capacity was affected and ranged from −2.5% to 7.75%. The amount of the carbon nanotube addition had a substantial impact on the beams’ application level and load-carrying capacity. Particularly, the application of 0.5 wt% additive in the outermost fiber region of the beams, such as in FGM-4, led to an increase in the bending capacity. However, the stiffness values at the maximum load were decreased by 0.3%–18.6% compared to FGM-1, with the minimum level of the decrease in FGM-4. The experimental results were compared with the theoretical calculations based on the high-order shear deformation theory, which yielded an approximation between 11.99% and 12.98% by applying the Navier’s solution.